The Transcultural Diabetes Nutrition Algorithm: A Middle Eastern Version - Hamdy, Osama; Al Sifri, Saud; Hassanein, Mohamed; Al Dawish, Mohammed; Al-Dahash, Raed A.; Alawadi, Fatheya; Jarrah, Nadim; Ballout, Hajar; Hegazi, Refaat; Amin, Ahmed; Mechanick, Jeffrey I. (Frontiers in Nutrition, 2022)
Diabetes prevalence is on the rise in the Middle East. In countries of the Gulf region—Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, and the United Arab Emirates—prevalence rates are among the highest in the world. Further, Egypt now ranks as one of the top 10 countries in the world for high number of people with diabetes. Medical nutrition therapy is key to optimal management of diabetes. Patient adherence to nutritional guidance depends on advice that is tailored to regional foods and cultural practices. In 2012, international experts created a transcultural Diabetes Nutrition Algorithm (tDNA) for broad applicability. The objective of this current project was to adapt the algorithm and supportive materials to the Middle East region. A Task Force of regional and global experts in the fields of diabetes, obesity, and metabolic disorders met to achieve consensus on Middle East-specific adaptations to the tDNA. Recommendations, position statements, figures, tables, and graphs are presented here, representing conclusions of the tDNA-Middle East (tDNA-ME) Task Force. Educational materials can be used to help healthcare professionals optimize nutritional care for patients with type 2 diabetes. The tDNA-ME version provides evidence-based guidance on how to meet patients’ nutritional needs while following customs of people living in the Middle Eastern region.